Respuesta :

[tex]\displaystyle \dfrac{\dfrac{4c^2-36}{8c^2-24c}}{\dfrac{12c+36}{2c^2 -6c}}\\\\\\=\left(\dfrac{4c^2 -36}{8c^2 -24c}\right) \cdot \left(\dfrac{2c^2 -6c}{12c+36}\right)\\\\\\=\left[\dfrac{4(c^2 -9)}{8(c^2-3)}\right]\cdot\left[\dfrac{2(c^2-3)}{12(c+3)}\right]\\\\\\=\dfrac{8(c^2-3^2)}{8 \cdot 12(c+3)}\\\\\\=\dfrac{(c+3)(c-3)}{12(c+3)}\\\\\\=\dfrac{c-3}{12}[/tex]

[tex]\text{Hence the answer is d.}[/tex]

Answer:

d

Step-by-step explanation:

separate the 2 divisions and simplify each , that is

[tex]\frac{4c^2-36}{8c^2-24c}[/tex] ← factor numerator/ denominator

= [tex]\frac{4(c^2-9)}{8c(c-3)}[/tex] ← factor difference of squares on numerator

= [tex]\frac{4(c-3)(c+3)}{8c(c-3)}[/tex] ← cancel (c - 3) and 4/8 on numerator/ denominator

= [tex]\frac{c+3}{2c}[/tex]

---------------------------------------------------

[tex]\frac{12c+36}{2c^2-6c}[/tex] ← factor numerator/ denominator

= [tex]\frac{12(c+3)}{2c(c-3)}[/tex] ← cancel 12 and 2 on numerator/ denominator

= [tex]\frac{6(c+3)}{c(c-3)}[/tex]

----------------------------------------------------------

to divide the top fraction by the lower fraction

leave top fraction, change division to multiplication, turn lower fraction upside down.

[tex]\frac{c+3}{2c}[/tex] × [tex]\frac{c(c-3)}{6(c+3)}[/tex] ← cancel (c + 3) and c on numerator/ denominator

= [tex]\frac{c-3}{2(6)}[/tex]

= [tex]\frac{c-3}{12}[/tex] → d

ACCESS MORE